Genotypic Characterization of Human Respiratory Syncytial Viruses Detected in Mexico Between 2021 and 2024 - Nadia Martínez-Marrero; Juan Carlos Muñoz-Escalante; Rosa Maria Wong-Chew; Pedro Torres-González; Miguel Leonardo García-León; Patricia Bautista-Carbajal; Pedro Antonio Martínez-Arce; María del Carmen Espinosa-Sotero; Verónica Tabla-Orozco; Fabian Rojas-Larios; Susana Juárez-Tobías; Ana María González-Ortiz; et al. (Viruses)
Human respiratory syncytial virus (HRSV) is a leading cause of severe respiratory infections among children, older adults, and immunocompromised individuals. The COVID-19 pandemic and the non-pharmacological interventions to mitigate it resulted in significant changes in HRSV epidemiology and seasonality patterns. Worldwide, there was a considerable reduction in the number of HRSV infections during that period, and the impact of those changes on genotype distribution is still not fully understood. In this work, we analyzed the genotypic characteristics of HRSV strains detected between 2021 and 2024 in Mexico with the aim of identifying changes in circulating lineages. HRSV positive samples collected in five states in Mexico were used. The complete viral attachment glycoprotein gene was sequenced, and phylogenetic inference was performed using datasets including all sequences available at GenBank and GISAID until 30 June 2024. We obtained 114 HRSV sequences (63.2% HRSV-A and 36.8% HRSV-B); 19 were from the 2021–2022 season, 53 from 2022–2023, and 42 from 2023–2024. All HRSV-A sequences clustered with sequences from other countries within A.D lineages, including A.D.1, A.D.3, A.D.5.1, and A.D.5.2 lineages. All HRSV-B sequences clustered in the B.D.E.1 lineage with sequences collected between 2020 and 2024. In conclusion, the characterization of HRSV viruses circulating in Mexico during and after the SARS-CoV-2 pandemic and comparison to all available sequences reported to date corroborates that, on a global scale, HRSV-A viruses of several A.D lineages circulate simultaneously, while HRSV-B viruses are restricted to the B.D.E.1 lineage.